‘Professional Techs’: Machines, Technical Skills and Professional Aspirations in Hearing Prosthetics and Respiratory Care in Quebec, 1950-1990 - Prud’homme, Julien (Scientia Canadensis, 2010)
In the sociology of professions, working with machines is often seen as an obstacle to professional aspirations. This is especially true in healthcare, where a sharp distinction between professionals and technicians has prevailed since the early 20th century. However, only a few studies have documented the meaning of machines and technical skills for healthcare technicians. The purpose of this article is to show how and why two groups of such technicians, hearing prosthetists and respiratory technicians, actually tried to reconcile the use of machines with professionalization projects. It concludes with considerations about what these stories tell us about the history of technical work, about the transformations of the healthcare work environment in the second half of 20th century, and about the place of technical skills in the system of professions